Underwater carnival: explaining how Thai boys’ love drama series “sneak” into Chinese media cyberspace - Zeng, Damei (2025)
Thai boys’ love (BL) drama series, which peddle romantic relationships between pretty male characters, are emerging as vibrant players in the global subculture market. This article investigates the intriguing phenomenon of how Thai BL drama series evade censorship and flow into Chinese media cyberspace. Our analysis focuses on two of the critical stakeholders in the geocultural flow of Thai BL genres: entertainment corporations and fan-subtitled groups. This research demonstrates that these two crucial actors have formed alliances to participate in the transnational relay of Thai boy intimate media, developing the synergistic “soft resistance” strategy centered on compromise and adaptation to counteract media censorship under the Chinese patriarchal political regime. The coordinated networks that have resulted from the interactive marketing tactics of producers and distributors have enabled Thai male bonding media to successfully penetrate the Chinese “cultural fence.” However, this successful infiltration of Thai BL drama series into the Chinese market should not be exaggerated. They remain a subdued “underwater carnival” outside the orthodox normative paradigms of heterosexuality in Chinese society.